2019
DOI: 10.32929/2446-8355.2019v28n1p19-28
|View full text |Cite
|
Sign up to set email alerts
|

Teste de patogenicidade dos isolados de Pyricularia oryzae nos hospedeiros de trigo, cevada, arroz e braquiária

Abstract: A Espécies de fungos do gênero Pyricularia estão associadas com a doença brusone em plantas da família Poaceae. Pyricularia oryzae é a espécie de maior incidência e distribuição mundial, causando perdas em culturas de importância econômica como arroz, aveia, centeio, cevada, trigo e triticale. Dessa forma, este estudo teve como objetivo caracterizar o espectro de patogenicidade de P. oryzae do trigo e plantas invasoras nos hospedeiros de trigo, braquiária, arroz e cevada. A pesquisa foi conduzida no Laboratóri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
(20 reference statements)
2
4
0
Order By: Relevance
“…The low frequency of wheat <-> Urochloa cross-infection found in nature seems to be correlated with innate compatibility differences because, using cross-inoculation experiments, we found that PoT members were consistently more aggressive on wheat leaves, and the isolates from Urochloa (PoU3/4 and Pu) were more aggressive on signalgrass. Thus, our findings hold to the general pattern that PoT is usually more aggressive on wheat, while non-PoT/non- P. oryzae isolates tend to be less aggressive, even under favorable, controlled environments (Chung et al 2020; Kato et al 2000; Reges et al 2016, 2019). And, even though the Urochloa pathogens showed incidences on the spikelets up to 50%, after spraying spikelets, the percent diseased area was apparently rather low, and the symptoms were mild, consisting of small, reddish-brown to dark-gray spots, or even hypersensitive reactions.…”
Section: Discussionsupporting
confidence: 76%
“…The low frequency of wheat <-> Urochloa cross-infection found in nature seems to be correlated with innate compatibility differences because, using cross-inoculation experiments, we found that PoT members were consistently more aggressive on wheat leaves, and the isolates from Urochloa (PoU3/4 and Pu) were more aggressive on signalgrass. Thus, our findings hold to the general pattern that PoT is usually more aggressive on wheat, while non-PoT/non- P. oryzae isolates tend to be less aggressive, even under favorable, controlled environments (Chung et al 2020; Kato et al 2000; Reges et al 2016, 2019). And, even though the Urochloa pathogens showed incidences on the spikelets up to 50%, after spraying spikelets, the percent diseased area was apparently rather low, and the symptoms were mild, consisting of small, reddish-brown to dark-gray spots, or even hypersensitive reactions.…”
Section: Discussionsupporting
confidence: 76%
“…Collectively, our results challenge the dominant hypothesis that signal grass is the major natural reservoir for the wheat blast pathogen (PoT) (Reges et al 2018(Reges et al , 2019Ceresini et al 2019;Dorigan et al 2019;Poloni et al 2021b). Actually, considering the strong association with its primary hosts in nature, phylogenetic relationships, and pathogenic specialization, signal grasses from MG are mainly infected by Urochloa pathotypes, regardless of their distance to wheat fields.…”
Section: Discussionsupporting
confidence: 56%
“…Triticum pathotype is usually more aggressive on their primary host, where the fungal colonization at the rachis vassel causes partial or complete head bleaching, leading to larger yield losses in favorable climate conditions at field conditions (Goulart and Paiva 2000;Goulart et al 2007;Urashima et al 2009;Pagani et al 2014). Instead, non-P. oryzae or non-PoT isolates demonstrated low aggressiveness when inoculated in wheat, even under controlled conditions (Kato et al 2000;Reges et al 2016Reges et al , 2018Reges et al , 2019Chung et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachiaria) have received greater attention regarding their possible interference in the wheat blast cycle because they are widely disseminated forages in the Brazilian agricultural system (CASTROAGUDÍN Ciência Rural, v.53, n.4, 2023. Maciel et al et al, 2016;REGES et al, 2016;REGES et al, 2019). An estimate made in 2012 indicated that the participation of species of the genus Urochloa as cultivated pasture in Brazil was 70% of a total area of about 117 million hectares (ZIMMER et al, 2012).…”
mentioning
confidence: 99%